Requirements and Terms of Derrida Reconstruction Theory in Critical Reading of Texts - Seyed Reza Shakeri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper can point to undeniable considerations in criticizing the literary text of Iran by presenting the correct and additional explanation of Derrida's deconstruction and its cognitive requirements, making it faster in the use of new theories and methods of European critique is in Iran. Mojtaba Golestani's book is also criticized for this failure. Thus, the article shows that in understanding, explaining and criticizing the works of contemporary Iranian writers, they should discuss these issues in order to understand the distance between the reader's world and the text for the reader of his own. The writer of the book deliberately as a researcher, like the modern subject, has transformed the texts of Ale Ahmad into the subjects of his research program and has not been able to communicate with the text. In this article, the process of objecting the texts is largely open in a critically acclaimed book. The result of this study is that the critique of the works of such people as Ale Ahmad Shamloo, Shariati, Nima and others is a function of their historical conditions and activities, which should be taken in a concise and balanced way.